2022
DOI: 10.1155/2022/7942506
|View full text |Cite
|
Sign up to set email alerts
|

The Effects of Dietary Thyme Oil (Thymus vulgaris) Essential Oils for Common Carp (Cyprinus carpio): Growth Performance, Digestive Enzyme Activity, Antioxidant Defense, Tissue and Mucus Immune Parameters, and Resistance against Aeromonas hydrophila

Abstract: This study evaluated the effects of dietary supplementation of thyme (Thymus vulgaris) essential oil (TVO) on growth performance, digestive enzymes, biochemical parameters, hematological indices, liver enzymes, and pathogen resistance in common carp (Cyprinus carpio). Triplicate groups of fish (15.36 ± 0.10 g) were fed daily with diets supplemented with TVO at 0, 0.5, 1, and 2 percent for 60 days then challenged with Aeromonas hydrophila. The results determined that supplementation of thyme resulted in signifi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(7 citation statements)
references
References 79 publications
2
5
0
Order By: Relevance
“…It is supposed that increase in the activity of these enzymes leads to better digestion. It has been shown that thyme essential oil improves growth performance concurrent with increase in the intestinal activity of digestive enzymes in common carp, Cyprinus carpio (Ghafarifarsani et al, 2022), which supports the present finding. The exact mechanisms of elevation of digestive enzymes are not clear, but it could be a direct effects of TV-NP on enzyme synthesis and release from pancreas, which needs further investigations.…”
Section: Discussionsupporting
confidence: 91%
See 3 more Smart Citations
“…It is supposed that increase in the activity of these enzymes leads to better digestion. It has been shown that thyme essential oil improves growth performance concurrent with increase in the intestinal activity of digestive enzymes in common carp, Cyprinus carpio (Ghafarifarsani et al, 2022), which supports the present finding. The exact mechanisms of elevation of digestive enzymes are not clear, but it could be a direct effects of TV-NP on enzyme synthesis and release from pancreas, which needs further investigations.…”
Section: Discussionsupporting
confidence: 91%
“…Wuchang bream, Megalobrama amblycephala, showed similar decrease in lysozyme activity 48 h after an experimental infection with A. hydrophila (Liu et al, 2012). It was shown that thyme essential oil can increase serum and mucosal lysozyme activities in rainbow trout (Zargar et al, 2019) and common carp (Ghafarifarsani et al, 2022), which support the present results. However, the present results show that pre-challenge plasma lysozyme activity is not a suitable predictor of survival after A. hydrophila infection, as shown in 100TV treatment.…”
Section: Discussionsupporting
confidence: 89%
See 2 more Smart Citations
“…Thyme is one of the medicinal plants with significant antioxidant properties [ 46 ]. Besides, thymol and carvacrol, as important antioxidant components of the extract, are monoterpenes whose effects are not dose-dependent [ 47 ]. Therefore, it is necessary to use and determine the effective dose in this regard [ 48 ].…”
Section: Discussionmentioning
confidence: 99%